(untitled) (Research, Society and Development, 2020)
The study aimed to characterize the epidemiological clinical profile of patients undergoing urgent and emergency surgical procedures. This is an epidemiological, cross-sectional, quantitative study. A hospital-based survey and an electronic medical record was used as a research instrument, with the location of the study in the operating room between January and November 2019. The sample used was 297 medical records. The study was approved by the ethics committee, under opinion No. 4,174,045, CAAE: 32207320.5.0000.0025. Through this study, a greater exposure of males was identified, with a predominance of 20 to 39 years old. A significant percentage of patients come from the Federal District. Regarding the district cities, these come from cities close to the hospital. The administration of antibiotic prophylaxis proved to be important and used in surgeries. As for the surgical specialty, he highlighted the most performed in general surgery, followed by orthopedic ones. Most had an emergent profile and with no comorbidity. It is essential that there is a defined and clarified plan, given the precise description of the specific activities and responsibilities of the Nursing team. It is believed that this study can contribute with information that support the adequacy of care, for the elaboration and updating of care protocols with regard to the performance of Perioperative Nursing, and thus, interventions to improve the care offered to patients of surgical demand.